National development and student politics in Bangladesh - Alam, Gazi Mahabubul; Rabby, Talukder Golam; Thian , Lok Boon; Khan, Issa; Hoque, Kazi Enamul (Academic Journal, 2011)
Student politics is one of the ignored areas in the international scholarly debate. In the late 1960's to early 1970's, some authors made some contributions in the context of South America and Africa. In 1968, Altbach also made very little contribution on the Indian student politics and its impact on development. The institutions of HE (higher education) in southern Asia is experiencing a high volume of student politics and teacher politics. In the discourse of institutional management and national development, people often make links between teacher politics and students while they talk informally. As the academics of HE in Southern Asia whom mainly conduct research are also rigorously involved with the politics, therefore, they often ignore this area. Factually, student politics has a serious impact on the institutional management and education system itself. This also provides a high volume of impact on the national development, education and state business in overall. This paper explores the impact of students' involvement in 'party politics' on national development and state business of education in Bangladesh, while answering some specific research questions through the data gained from an empirical research work.